Using the chemistry classroom as the starting point for engaging urban high school students and their families in pro-environmental behaviors. Issue 1 (2nd January 2017) - Daubenmire, Patrick L.; van Opstal, Mary T.; Hall, Natalie J.; Wunar, Bryan; Kowrach, Nicole
ABSTRACT: Evolving mobile technology and the rapid spread of STEM-focused informal learning environments have created a unique opportunity to break through the barriers that have traditionally separated diverse learning contexts such as school, family, and community. Previous research suggest that in a well-designed family learning environment, both parents and children can make significant gains in science knowledge, science skills, and positive attitudes toward science, and academic self-efficacy. Families, Organizations, and Communities Understanding Science, Sustainability, and Service (FOCUSSS) is a design-based research project created to blur the boundaries between formal and informal learning contexts: chemistry classrooms (formal environments) and at-home, local, and museum (informal environments). In doing so, adoption of real-world, pro-environmental behaviors can be promoted to have tangible positive impacts on individuals, families, communities, and the environment. Data from this two-year program support that cutting across contexts does indeed correlate with increased self-efficacy in science and positive changes in pro-environmental behavior. Furthermore, the FOCUSSS design framework appears to be quite robust, delivering consistent results across variations including teacher, grade level, school type (neighborhood, charter, private), and parent education.